Perbedaan Cakupan Imunisasi Campak Pada Bayi Antara Puskesmas Desa Dan Kota Di Kabupaten Sukoharjo Periode Juli 2015 - Juni 2016 - Hapsari, Deby; , Prof. Dr. H. Bambang Soebagyo, dr., Sp.A (K) (2017)
Immunization Development Program (IDP) is implemented by ministry of health due to reduce the number of disease that can be prevented by immunization for children, e.g., easles. Measles immunization coverage in Indonesia tend to be higher in town than rural. It can be happened due to factors that influence the immunization coverage in rural and urban. The aim of this research is to know the differences of infants measles immunization coverage between rural and urban primary health care in Sukoharjo district and find the factors that make them different. This research is a descriptive using qualitative research and interview about measles immunization with total sampling technique. The result is the number of measles immunization coverage in the rural public health care is 92.9%, whereas urban primary health care is 98.8%. There is a difference in the percentage of measles immunization coverage in the rural about 5.9%, due to socioeconomic condition, facilities and health workers, and communication. The conclusion of this research is there is a difference of infants measles immunization coverage that in urban primary health care higher than rural public health center in Sukoharjo from July, 2015-June, 2016. Keywords: Measles immunization, Rural Primary Helath Care, Urban Primary Health Care